Effect of Fabrication Method and Heat Treatment on the Properties of Co-Cr Bio Alloy - Hanoon, Zahraa A.; Jabur, Adnan S. (Basrah Journal for Engineering Sciences, 2023)
Co-Cr alloys are widely used in dental and medical equipment since the development of the first cast Co-Cr-Mo alloy. This is due to its high mechanical properties and high resistance to wear and corrosion. This research aims to study the effect of the fabrication method (Investment Casting and Selective Laser Melting SLM by 3D printing) and heat treatments on the mechanical and tribological properties of Co-Cr-Mo alloy. It was found that the Selective Laser Melting method in general increases the ultimate tensile strength, strain and hardness compared to the Investment Casting method. Also, solution treatment and aging reduce the strength and strain values of the SLM samples and have no obvious effect on the casting samples. The wear test shows that wear rate of casting samples is lower than that of SLM samples.